التقويم السيكومتري للنسخة الجزائرية لمقياس التقرير الذاتي - زياد, رشيد (جامعة الوادي University of Eloued, 2017)
تهدف دراستنا الحالية إلى التحقق والتقويم السيكومتري للنسخة الجزائرية لمقياس فرط الحركة وقلة الانتباه عند الراشدين (ASRS v1.1) لـ(كيسلر وآخرون،2005)، على عينات مختلفة مكونة من 433 شخص أعمارهم تراوحت ما بين 17-58 سنة، تم التحقق من مؤشرات الثبات بالطرق التالية (الاتساق الداخلي بألفا كرونباخ، وثبات الاعادة أو الاستقرار)، كما تم التحقق من مؤشرات الصدق من خلال (الصدق الظاهري، والاتساق الداخلي بارتباط الدرجة الكلية بالبند، والصدق التقاربي والتباعدي باستخدام مقياس الاكتئاب والقلق والضغط النفسي (DASS21) وقائمة أكسفورد للسعادة (OHI)، والصدق التمييزي بطريقة الفرق المتقابلة، والصدق العاملي بطريقة التحليل العاملي الاستكشافي والتوكيدي). أشارت نتائج النسخة الجزائرية لمقياس فرط الحركة وقلة الانتباه عند الراشدين (ASRS v1.1) لمؤشرات الصدق والثبات العالي، وهو ما يسمح بترشيح الأداة موضع الإهتمام للاستخدام سواء للأغراض البحثية أو التشخيصية في البيئة الجزائرية. The current study aims to verify and Psychometric Evaluation of the Algerian version of Attention –Deficit/Hyperactivity in adults (ASRS v1.1) (Kessler et al., 2005). On different samples composed of 433 people ages ranged from 17-58 years old. Reliability indicators were verified using the following ways (Cronbach’s alpha coefficient of internal consistency and reliability of stability). Validity indicators were confirmed through (face validity and internal consistency of the item total correlation, Convergent and divergent validity using depression, anxiety and stress scale (DASS21) and Oxford Happiness Questionnaire (OHQ), discriminatory validity and factorial validity using Exploratory and confirmatory factor analysis. The results of Algerian version of Attention –Deficit/Hyperactivity Scale in adults (ASRS v1.1) showed high indicators of validity and reliability, which allows the nomination of the instrument of interest to be used for either research or diagnostic purposes in the Algerian environment
لاضطراب فرط الحركة وقلة الانتباه عند الراشدين
مقال
Keywords: التقويم السيكومتري؛ مقياس (ASRS-v1.1)؛ (ADHD) عند الراشدين; Psychometric Evaluation, Scale (ASRS-v1.1), (ADHD) in adults